Convergence of Generalized Quasi-Nonexpansive Mappings in Hyperbolic Space - Naeem Saleem; Maliha Rashid; Fahd Jarad; Amna Kalsoom (Journal of Function Spaces)
In this article, we consider a wider class of nonexpansive mappings (locally related quasi-nonexpansive) than monotone nonexpansive mappings. We obtained the convergence of fixed point for quasi ϱ-preserving locally related quasi-nonexpansive mappings in hyperbolic space. An iterative process is also used to obtain the convergence results for this mapping. Fixed point is approximated numerically in a nontrivial example by using Matlab.